Translation Shifts Found in Public Signs at Airport - Inna Nurin Annisa; I Komang Sulatra (Institut Agama Islam Negeri Palopo, 2024)
This study examines translation shifts in public signs at I Gusti Ngurah Rai International Airport, applying Catford's category shifts (1965). It emphasizes the importance of maintaining both semantic meaning and stylistic elements during the translation process between the source language (SL) and the target language (TL). The research identifies four distinct types of category shifts: structure, unit, class, and intra-system. Data were gathered through observations of 52 public signs. The findings reveal that structure shifts are the most prevalent, accounting for 52% of the identified shifts, followed by unit shifts at 28%, class shifts at 16%, and intra-system shifts at 4%. These results highlight the necessity for structural adaptations to ensure effective translation in public signage. Additionally, the study underscores the importance of employing diverse translation techniques to facilitate clear communication in an international airport environment.